Responses to textual and pictorial cigarette pack health warnings: findings from an exploratory cross-sectional survey study in Austria - Hannes Mayerl; Erwin Stolz; Wolfgang Freidl (BMC, 2018)
Abstract Background Packaging and labelling tobacco products has emerged as an effective policy to reduce the global health burden of tobacco use. The main purpose of this study was to explore Austrian smokers' and ex-smokers' responses to both the textual and pictorial cigarette pack health warnings (CPHWs) recently implemented. Methods We analysed self-reported data (N=500) from an Austrian cross-sectional survey that was conducted after the implementation of the new pictorial CPHWs in 2016. Results The results showed only weak effects of the CPHWs on the decision to quit or reduce smoking, and the level of impact of the CPHWs remained limited particularly because of smokers denying the ill-effects of tobacco use. Conclusions Although the CPHWs seem to have the potential to promote a change in smoking behaviour, the warnings reached only a rather small group of smokers, while the majority of smokers appeared to remain unaffected by this intervention. Public health policies are challenged to increase the salience of CPHWs and to overcome smokers' denial of detrimental health effects.